1976
DOI: 10.1017/s0043174500066261
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Control of Field Horsetail

Abstract: Soil-incorporated treatments of dichlobenil (2,6-dichlorobenzonitrile) at 4.5 or 9 kg/ha completely controlled field horsetail (Equisetum arvense L.) for 2 yr and at 9 kg/ha, control was 90 to 99% in the third year. Mulching with sawdust after surface application of dichlobenil gave similar results. In an area treated at 9 kg/ha and isolated from emerged field horsetail, there was no reappearance of field horsetail until 5.5 yr after treatment. Japanese holly (Ilex crenata Thunb.) and azalea (Rhododendron X ‘R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Complete regrowth of quackgrass oc curred by the end of the second season. On the basis of pre vious work, some kinds of woody ornamentals could be expec ted to make normal growth if planted a year following such a treatment (18).…”
Section: Resultsmentioning
confidence: 99%
“…Complete regrowth of quackgrass oc curred by the end of the second season. On the basis of pre vious work, some kinds of woody ornamentals could be expec ted to make normal growth if planted a year following such a treatment (18).…”
Section: Resultsmentioning
confidence: 99%
“…All the treatments were applied in late summer or autumn in the field trial, which is recommended as the best time to obtain translocation and activity against the root system due to the significant rhizome growth at this time (Marshall 1986). The results from other studies showed greater levels of control (Hoyt & Carder 1962;Patterson 1965;Ryan 1976) but they were conducted in cropping areas where there are water and other stresses to aid herbicide efficacy.…”
Section: Regrowth Of Root Fragments In Glasshousementioning
confidence: 88%
“…There appears to be a dearth of recent publications on the control of field horsetail, possibly because some 40-50 years ago it was claimed that several herbicides readily controlled this weed (Hoyt & Carder 1962;Patterson 1965;Ryan 1976). The recommended herbicides were amitrole, picloram and dichlobenil respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Malheureusement, la majorite des interventions herbicides de post-levee effectuees en plein dans les cultures de cereales a paille et de mais, doivent etre faites au debut du mois de juin, au moment de la levee des premieres tiges de la prele. L'amitrole, un herbicide a action totale (Ryan, 1976;Coupland & Peabody, 1981;Marshall, 1982), et le dichlobenil (Ryan, 1976;Coup-land & Peabody, 1981;Davison & Bailey, 1982) ont deja donne une repression efficace de la prele des champs durant une periode de deux a trois ans, L'utilisation d'herbicides selectifs pour reprimer les annuelles a feuilles larges dans des champs de seigle (Secale cereale L.) d'AUemagne de Test, aurait favorise la propagation de la prele (Karch & Sped, 1979), Dans des champs de cereales et de betterave sucriere de l'Allemagne federale, la couverture de l'espece dans des peuplements de vegetaux traites avec des herbicides a augmente en moyenne de 6% par rapport a celle de la mauvaise herbe dans les champs non traites (Callauch, 1981), Marshall (1984) deplorait qu'aucune etude systematique n'ait ete effectuee pour mesurer reff"et de successions de traitements herbicides utilisees dans les cultures sur des peuplements de prele des champs. Cet article presente les resultats d'experiences realisees afin de mesurer: (1) Tinffuence des cultures d'orge de printemps et de mais-grain sur revolution de trois peuplements de prele des champs; (2) l'eff'et de programmes d'interventions herbicides soup<;onnes comme les plus efficaces dans l'orge et le mais-grain cultives en rotation, sur un peuplement dense de cette adventice.…”
Section: Introductionunclassified